An Epidermal Cyst in the Floor of the Mouth: A Rare Presentation - Suraj Mammen; Anu Korulla; Paul M.J. (Journal of Clinical and Diagnostic Research, 2013)
ABSTRACT Epidermal cysts rarely occur in the head and neck region as compared to the dermoid cysts and when they do occur in this region, they present in the floor of the mouth. We are reporting a rare case of an epidermal cyst in the floor of the mouth, with a brief review of the literature.